50 days of war on innocent civilian: Ma’an news agency coverage of Israeli and Palestinian conflict - Almahallawi, Wesam; Zanuddin, Hasmah (Science Publishing Corporation, 2018)
Since the TV broadcasting was established in Arab countries until the 1990s, broadcasting during this specific time was based on a government control model, which derived from the view of broadcasting as an instrument of state advance that must be under the control from government. This kind of TVs, limits the broadcasting to highlight the government issue (1). In these kind of TVs, they focus with the leader's opinion more than the Palestinian problem. By the way, the theme in Arab media determined to highlight the leader's opinion who claims the right to speak on behalf of Palestinians. In September 1991, the first private TV in the Arab world was established when MBC went on the air from London. More private TVs followed after that like: Orbit in 1994 and ART in 1995, both based in Italy owned by Saudi businessmen, Future Television and LBC, both Lebanese based in Beirut, in 1995, and Al-Jazeera based in Qatar in 1996. In 2002 the number of the Arab TV stations was expanded to more than 150 TVS as government or privately owned, with capability of reaching the Arab people in any place in the world. This paper focuses on the media coverage of the conflict between two parties Palestine and Israel. The preview studies show that, in a conflict the media has an influential role and has responsibility for increasing violence or contributing to the resolution of conflict and mitigation of violence (2). This study examined 61 news coverage and framing of the Israel and Palestine conflict, known as the 50 days' war from 8 July - 26 August 2014 by Ma'an News Agency, which delivers news to Ma'an TV (Palestinian satellite television station). A quantitative content analysis was employed to examine the news published during the war using five generic frames developed by (3). Holsti Inter-coder reliability and validity test value is 0.988 or 98% agreement. The results showed that conflict and human-interest frames were significantly visible compared to other frames in Ma'an news coverage. Portrayal of images of civilian killing, children and women killed in their homes and suffrage news coverage, in this war. Responsibility frame stressed on hospitals bombing and embargo of medications which reduced chances for Palestinian of immediate medical help. The economic frame highlighted the economic and financial losses of Palestinians as consequences of 50 days' war. Most of them lost their income, businesses, agriculture land and homes and became refugees.